Investigating the Role of I Kappa B Kinase ε in the Pathogenesis of Psoriasis - Isabella Weimar; Pernille Ommen; Lars Iversen; Claus Johansen (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)